Vaccine route, dose and type of delivery vector determine patterns of primary CD8+ T cell responses. - Estcourt, M; Létourneau, S; Mcmichael, A; Hanke, T (2005)
The dynamics of primary CD8+ T cell responses following administration of modified virus Ankara (MVA)- and DNA-vectored vaccines was investigated in a mouse model. To overcome the low frequency of naive antigen-specific precursors and follow the early expansion events, naive CFSE-labelled T cell receptor-transgenic F5 lymphocytes were transferred into syngeneic non-transgenic recipients prior to vaccination. Using the i.d., i.v. and i.m. routes and increasing recombinant MVA (rMVA) vaccine doses, the primary response was analysed on a divisional basis at local and distant lymphoid organs at various times after vaccination. The results indicated that F5 cell divisions were initiated in the local draining lymph nodes and cells only after five to six divisions appeared at more distant sites. The rMVA dose affected frequencies of cells entering division and at the peak response. When priming induced by rMVA and plasmid DNA was compared, dramatic differences in the cycling patterns were observed with plasmid DNA inducing a response slower and more sustained over the first 2 wk than rMVA. Both rMVA and DNA induced comparable IFN-gamma production, which increased with cell divisions. Taken together, the vaccine type, dose and route have a strong influence on the spatial and temporal patterns of initial T cell responses.